The Cytotoxic and Antileishmanial Effects of Satureja khuzestanica Essential Oil - Farnaz Kheirandish; Rouzbeh Chegeni; Bahram Delfan*; Mahboubeh Jabari; Farzad Ebrahimzadeh; Marzieh Rashidipour (Lorestan University of Medical Sciences, 2016)
Background and Aim: Leishmaniasis is endemic in 98 countries including Iran. Pentavalent antimony compounds resistance as first-line therapy is increasing in some local areas. Also side effects of these drugs are limited at the beginning of treatment, but the toxicity increases with time. The aim of this study was to assess the effect of Satureja khuzestanica essential oil (SKEO) on promastigote and amastigote Leishmania major forms. Materials and Methods: The components of S. khuzestanica oil were identified by gas chromatography/mass spectroscopy (GC/MS) analysis. To evaluate antipromastigote activity the different concentrations of extract  and glucantime were added to the wells that contained L. major. The plates were incubated at 26±1°C for a week. On days 1, 3 and 5, the number of live promastigotes in each well was counted. For assessment of SKEO effect on intracellular amastigotes, mouse peritoneal macrophages were isolated and infected with promastigotes. Different concentrations of the extract and glucantime were added to the cultures. The cultures were incubated at 37°C and CO2 5%. The number of infected macrophages and amastigotes within each macrophage were counted. Toxicity assessment of SKEO on macrophages was done by MTT method. Results and Conclusions: The mean number of promastigotes, infected macrophages and amastigotes in a macrophage in the control and treated groups had significantly difference. So that their number in the treated groups was less as a dose-dependent response. The present research showed potent antileishmanial activity of, SKEO; additionally this plant had no toxic effect on mammalian cells.